2021
DOI: 10.2196/25277
|View full text |Cite
|
Sign up to set email alerts
|

The Resilience of Cardiac Care Through Virtualized Services During the COVID-19 Pandemic: Case Study of a Heart Function Clinic

Abstract: Background: Virtual care has historically faced barriers to widespread adoption. However, the COVID-19 pandemic has necessitated the rapid adoption and expansion of virtual care technologies. Although the intense and prolonged nature of the COVID-19 pandemic has renewed people's interest in health systems resilience, which includes how services adapt or transform in response to shocks, evidence regarding the role of virtual care technologies in health systems resilience is scarce.Objective: At Toronto General … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…For example, Gifford et al [ 66 ] reported the way in which wards and outpatient clinics rapidly converted to “digital” wards involving e-health, video and phone consultations. Alternatively, in one study from Canada [ 68 ], a lack of appropriate technology impeded resilient performance, with the rapid but “piecemeal” adoption of multiple virtual care technologies during COVID-19 resulting in systems that duplicated administrative work for healthcare professionals.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Gifford et al [ 66 ] reported the way in which wards and outpatient clinics rapidly converted to “digital” wards involving e-health, video and phone consultations. Alternatively, in one study from Canada [ 68 ], a lack of appropriate technology impeded resilient performance, with the rapid but “piecemeal” adoption of multiple virtual care technologies during COVID-19 resulting in systems that duplicated administrative work for healthcare professionals.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies highlighted a spike in the use of different technologies to enable the provision of patient care in different settings 38 45 53 54 57 58 68 71 74–77. Dunleavy and colleagues54 described the adoption of new technology to manage diabetes care during the pandemic such as the use of web-linked glucometers, electronic patient records, online referral systems and videoconferencing tools.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 10 lessons, derived from 61 studies [7,8,[10][11][12][14][15][16][17]19,20,23,25,28,30,33,39,43,45,[48][49][50][51]54,55,57,58,60,63,65,67,[71][72][73]78,82,83,85,91,96,101,116,118,[121][122][123]129,131,[136][137][138][140]…”
Section: Pillar 8: Operational Support and Logistics And Supply Chainsmentioning
confidence: 99%